2011
DOI: 10.1007/s13197-011-0588-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xanthan, guar, carrageenan and locust bean gum addition on physical, chemical and sensory properties of meatballs

Abstract: This study evaluated the effects of xanthan gum, guar gum, carrageenan and locust bean gum on physical, chemical and sensory properties of meatballs. Meatball samples were produced with three different formulations including of 0.5, 1, and 1.5% each gum addition and gum added samples were compared with the control meatballs. Physical and chemical analyses were carried out on raw and cooked samples separately. Moisture contents of raw samples decreased by addition of gums. There were significant decreases (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 42 publications
3
23
0
16
Order By: Relevance
“…Similarly, Demirci et al (2014) reported that the pH values of uncooked and cooked meatballs with different gums changed in the range of 6.7 to 6.9. Yılmaz (2004) determined that the pH value of meatballs with 5, 10, 15, and 20% rye bran ranged from 6.02 to 6.09.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, Demirci et al (2014) reported that the pH values of uncooked and cooked meatballs with different gums changed in the range of 6.7 to 6.9. Yılmaz (2004) determined that the pH value of meatballs with 5, 10, 15, and 20% rye bran ranged from 6.02 to 6.09.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, xanthan gum is a beneficial hydrocolloid because it is soluble in both hot and cold solutions, and binds water rapidly and very effectively. It permits the almost immediate preparation of viscous mixtures and ameliorates the emulsifying process of w/o emulsions . The higher encapsulation efficiencies of stored w/o/w emulsions were also observed when arabic gum was taken.…”
Section: Resultsmentioning
confidence: 99%
“…Os estabilizantes também auxiliam no aumento da viscosidade dos ingredientes e ajudam a evitar a formação de cristais que afetariam a textura do produto. São exemplos destes aditivos, as gomas xantana e guar (BRASIL, 1997;DEMIRCI et al, 2014).…”
Section: Efeito Da Utilização De Gomas Na Viscosidade E Nas Caracteríunclassified